Menelusuri asal usul sapi bali dengan menggunakan metoda analisis sitogenetik - Mustandi Surjoatmodjo (Hemera Zoa, 1993)
In order to study the origin of Bali cattle, the cytogenetic analyses of several breed of cattle (the Bali, Madura, Rambon, Bali-Taurus and Bos-Taurus) were carried out. The relative length of chromosome pairs were compared each other, and the values obtained from them were analysed by t test.The Bali cattle have much more chromosome pairs wich differ with the Bos taurus than other local cattle breed. It means that the Bali cattle have the longest genetic distance in relation to Bos taurus compared with the other domestic cattle (Bos). Hitherto, it has been understood that the Bali cattle had been domesticatedfrom banteng.